Kepemimpinan Otentik Kuntoro Mangkusubroto: Model Manajemen Integritas dan Etika Kepedulian Publik dalam Pemberdayaan Masyarakat Pascabencana NAD-Nias - Fanani, Muh. Asdig (Mafa Press, 2026)
Global humanitarian dynamics are at a nadir due to a surge in aid requirements disproportionate to budget availability and the erosion of integrity ecosystems. This research analyzes Kuntoro Mangkusubroto's leadership model at BRR NAD-Nias (2005-2009) as a transformative solution to the risks of corruption and politicization of disaster aid. Utilizing a descriptive qualitative method with a prominent figure study approach and thematic analysis, data were collected through audiovisual digital documentation and academic literature. The results show that integrating spiritual values (adl, rahma, khalifah) into authentic leadership pillars creates a robust moral defense mechanism. The political shield and no-cash policy strategies effectively mitigated state capture corruption. Furthermore, GIS/GPS-based lifecycle auditing technology transformed accountability into comprehensive transparency that maintains international trust. These findings prove that technocratic effectiveness must be accompanied by a public ethics of care to restore the dignity of survivors and foster community empowerment based on social resilience, cultural legitimacy, and sustainable livelihoods. The implication suggests a necessary transformation in disaster governance through institutionalizing real-time technological audits and institutional independence, alongside the integration of authentic leadership values into educational curricula to produce future leaders possessing “integrity DNA” and adaptive resilience toward future crises.